A retrospective observational study of ocular firecracker injuries during Diwali in the year 2023 encountered at a tertiary care hospital in Ahmedabad, Gujarat, India - Parmar, Neha; Patel, Yashvi; Garasia, Sneha; Prajapati, Vaishali; Vaghela, Arohi; Singhal, Deepika (International Journal of Research in Medical Sciences, 2026)
Background: Firecrackers are used worldwide to express festive mood inspite of the fact that they can cause severe mental and physical morbidity. Consequently, ocular injuries caused by firecrackers have become a national problem in different countries. The aim was to study the demographic pattern, clinical features, management and prognosis of the patients with firecracker-related ocular injuries during Diwali. Methods: This institution-based retrospective study was done on patients who attended eye emergency and outpatient department (OPD) of tertiary care center in Ahmedabad, Gujarat. The parameters studied were the age and sex of the patients, severity of injury with respect to active and passive participants, management, severity of injury and visual outcome with respect to type of firecrackers. Results: A total of 30 patients attended eye OPD and emergency during our study period, of which 91% were male and 9% were female. All of them were of variable age group. All patients were examined on the day of injury. Patients less than 20 years of age were most commonly affected. Visual acuity varied from 6/9 to no perception of light. The most common firework involved was the crackers. Conclusions: Careless and indiscriminate use of firecrackers may sometimes lead to serious ocular damage. In India, use of fireworks is quite common during various festivals, particularly during Diwali, thus fireworks-related ocular injuries are important causes of blindness. This retrospective study revealed the presentation and outcome of ocular injuries due to firecrackers in this area of mixed culture during this festive week.